2018
DOI: 10.7717/peerj.5834
|View full text |Cite
|
Sign up to set email alerts
|

Infection and coinfection by human papillomavirus, Epstein–Barr virus and Merkel cell polyomavirus in patients with squamous cell carcinoma of the larynx: a retrospective study

Abstract: BackgroundHuman papillomavirus (HPV) is recognized as an important risk factor for laryngeal carcinogenesis. Although HPV-16 and 18 have been strongly implicated, the presence of other high-risk HPV (HR-HPV) genotypes or the coinfection with Epstein-Barr virus (EBV) or Merkel cell polyomavirus (MCPV) may increase the risk, but their etiological association has not been definitively established.MethodsWe characterized the genotype-specific HPV and the frequency of EBV and MCPV infections through the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 44 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…Our results also support the paradigm of HPV as the predominant virus in OPSCC. Although several viruses have been detected in HNSCC, the most important viruses are HPV in OPSCC and EBV in NPC [ 1 3 , 5 , 14 , 26 ]. The etiologic role of HPV and EBV in the pathogenesis and prognosis of OPSCC and NPC, respectively, is well-established [ 1 , 2 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also support the paradigm of HPV as the predominant virus in OPSCC. Although several viruses have been detected in HNSCC, the most important viruses are HPV in OPSCC and EBV in NPC [ 1 3 , 5 , 14 , 26 ]. The etiologic role of HPV and EBV in the pathogenesis and prognosis of OPSCC and NPC, respectively, is well-established [ 1 , 2 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyomaviruses have been detected in various cancers [3,7,23,25,26]. The etiological role of Merkel cell polyomavirus in Merkel cell carcinoma is well-established [25], and various polyomaviruses have also been found in HNSCC [3,26]. Polyomaviruses may work as cofactors in malignant transformation and tumor progression [3,27].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the incidence of laryngeal cancer is closely related to Epstein Barr virus (EBV) infection and pointed out that HR-HPV infection plays a certain role in inducing laryngeal cancer 19. In recent years, although a few studies 27 have examined the infection frequency of HPV and EBV in LSCC tissue samples, the role of the different HR-HPV genotypes and EBV in the etiology of LSCC has not been further studied. One study showed a significant correlation between tumor size and lymph node metastasis with combined versus single infection 62.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported the presence of high-risk HPV in a subset of oral carcinomas from Chilean patients [18]. Thus, a possible collaboration between HPV and MCPyV in head and neck cancer is an interesting point that needs to be investigated in the future, as previously reported in laryngeal cancer [34].…”
Section: Discussionmentioning
confidence: 65%